Biological therapies in nonsmall cell lung cancer. Issue 3 (2nd March 2017) - Zugazagoitia, Jon; Molina-Pinelo, Sonia; Lopez-Rios, Fernando; Paz-Ares, Luis
Biological therapies have improved survival outcomes of advanced-stage nonsmall cell lung cancer (NSCLC). Genotype-directed therapies have changed treatment paradigms of patients with EGFR -mutant and ALK/ROS1 -rearranged lung adenocarcinomas, and the list of druggable targets with demonstrated clinical actionability ( BRAF, MET, RET, NTRK1 and HER2 ) continues to expand. Furthermore, we have incrementally understood the mechanisms of cancer immune evasion and foresee ways to effectively circumvent them, particularly at the immune checkpoint level. Drugs targeting the tumour immune-evasive PD-1 pathway have demonstrated remarkable treatment benefits in this disease, with a non-negligible fraction of patients potentially receiving long-term survival benefits. Herein, we briefly discuss the role of various medical disciplines in the management of advanced-stage NSCLC and review the most relevant biological therapies for this disease, with particular emphasis in genotype-directed therapies and immune checkpoint inhibitors. Genotype-directed therapies and immune checkpoint inhibitors have improved survival of subset of advanced NSCLC http://ow.ly/4EuI308cjl5